FEMALE SURGICAL STERILIZATION AT A TERTIARY CARE HOSPITAL IN KARACHI - Bhutta, Shereen Zulfiqar; Zaeem, Shabana; Korejo, Razia (Journal of Ayub Medical College Abbottabad, 2004)
Background: Tubal ligation for sterilization is one of the common methods of contraception practiced by women in developing countries like Pakistan. This study was undertaken to study characteristics of couples undergoing surgical sterilization, and to identify ways of improving utililization of contraceptive services. Material and methods: Details of 1148 women who underwent tubal ligation at the reproductive health center Jinnah Postgraduate Medical Center Karachi from January to December 2002 were recorded on a special proforma. The woman's age, duration of marriage, number of living children and the couple's educational status were recorded. Contraceptive use and duration, and associated medical conditions were documented. Data was entered in SPSS, frequency tables, means and standard deviations were obtained and comparative evaluation undertaken using non parametric methods, as indicated. Results: Out of the 4210 initial clients, 1163 (27.62%) underwent surgical sterilization. This included 1148 (98.69%) tubal ligations and 15 (1.31%) vasectomies. Of these, 608 (52.96%) were carried out in the immediate puerperium. The mean age of women was 33.1±3.55 years, they had been married for 14.84±4.22 years and 44.34% had already had 6 or more children. Conclusion: Tubal ligation performed after careful selection and counseling, by experienced personnel under local anaesthesia is a safe procedure with very few complications. However older women with no history of contraception, who have already had 6 or more children, seem to avail it. Promotion of temporary contraceptives for birth spacing among younger couples is more likely to improve maternal and newborn health in addition to limiting the family size. Key words: Female surgical sterilization, tubal ligation, age, parity, counseling, birth spacing